Effect of soybean meal or whole soybean on chemico-bromatologic composition of the soybean milk - Lourenço, Ewerton; Andrade, Pedro de; Andrade, Antonio Tadeu de; Sampaio, Alexandre Amstalden Moraes; Oliveira, Mauro Dal Secco de (Pesquisa Agropecuaria Brasileira, 2014)
The present research was conducted to analyse the effects of cooking time (two, four, and six hours) and temperature (50ºC, 65ºC and 80ºC) and the effects of soybean (Glycine max L.) meal or whole soybean in the chemico-bromatologic composition, levels of some minerals, milk production performance, pH and milk ureatic activity. The results showed no important differences among the cooking time means. In conclusion, soybean milk can be prepared with a cooking time of two hours. With respect to the temperature, it has an important effect, lowering the ureatic activity to satisfactory levels. This effect was more conspicuous when 80ºC was achieved, but such temperature also lowered the mean weight of the soybean milk (P<0.05). Concerning the substracts, whole soybean flour presented values significantly higher in relation to the ones presented by whole soybean meal. These values include higher values of dry matter, crude protein, ether extract, manganese, zinc and higher amount (weight) of soybean milk and also higher pH value (P<0.05), However, soybean meal provided milk with levels of total carbohydrates, mineral matter, K, P, Mg, Fe, and Cu higher than those of whole soybean.